Bacterial agents causing meningitis during 2013-2014 in Turkey: A multi-center hospital-based prospective surveillance study - Ceyhan, Mehmet; Ozsurekci, Yasemin; Gurler, Nezahat; Oncel, Eda Karadag; Camcioglu, Yildiz; Salman, Nuran; Kara, Ahu (Taylor & Francis Inc, 2016)
This is an observational epidemiological study to describe causes of bacterial meningitis among persons between 1 month and 18 y of age who are hospitalized with suspected bacterial meningitis in 7 Turkish regions. covering 32% of the entire population of Turkey. We present here the results from 2013 and 2014. A clinical case with meningitis was defined according to followings: any sign of meningitis including fever, vomiting, headache, and meningeal irritation in children above one year of age and fever without any documented source, impaired consciousness, prostration and seizures in those < 1 y of age. Single tube multiplex PCR assay was performed for the simultaneous identification of bacterial agents. The specific gene targets were ctrA, bex, and ply for N. meningitidis, Hib, and S. pneumoniae, respectively. PCR positive samples were recorded as laboratory-confirmed acute bacterial meningitis. A total of 665 children were hospitalized for suspected acute meningitis. The annual incidences of acute laboratory-confirmed bacterial meningitis were 0.3 cases / 100,000 population in 2013 and 0.9 cases/100,000 in 2014. Of the 94 diagnosed cases of bacterial meningitis by PCR, 85 (90.4%) were meningococcal and 9 (9.6%) were pneumococcal. Hib was not detected in any of the patients. Among meningococcal meningitis, cases of serogroup Y, A, B and W-135 were 2.4% (n = 2), 3.5% (n = 3), 32.9% (n = 28), and 42.4% (n = 36). No serogroup C was detected among meningococcal cases. Successful vaccination policies for protection from bacterial meningitis are dependent on accurate determination of the etiology of bacterial meningitis. Additionally, the epidemiology of meningococcal disease is dynamic and close monitoring of serogroup distribution is comprehensively needed to assess the benefit of adding meningococcal vaccines to the routine immunization program.
Keywords: epidemiology; etiologic agents; hospital surveillance; Meningitis; Turkey